G73 Paediatric difficult airway equipment in emergency departments: a regional audit. (27th April 2015) - Radia, T; Bernard, S; Rainsley, V; Florman, K; Chen, Q; Jaffer, M
Abstract : Aims: The 4th National Audit Project by the Royal College of Anaesthetists highlighted that difficult intubations account for 9% of all intubations in emergency departments (EDs). 1 It subsequently recommends that all paediatric EDs should have a difficult airway trolley (DAT) dedicated to paediatric use. The 2012 emergency care standard by RCPCH 4 also specified a list of recommended airway equipment in emergency situations. Previous surveys demonstrated a general low availability of a paediatric DAT in anaesthetics departments (16%) 2 and PICU/HDUs (42%). 3 This audit aims to survey the availability of paediatric DATs and difficult airway equipment in regional paediatric emergency units. Methods: A standard questionnaire for DAT and difficult airway equipment was devised according to the RCPCH guideline. 4 In February 2014, data was collected from senior nursing staff in all 34 regional paediatric EDs via telephone, email or in person. Results: 30 out of 34 units were included. Only 40% had a paediatric DAT on the unit, although all units had some paediatric difficult intubation equipment. A significant number of departments did not have capnography recording (23%), cuffed endotracheal tubes of all sizes (33%), or a cricoidotomy set (33%). Variation in the choice of laryngeal blades reflected individual preferences by specialists. 90% of units kept a daily checking rota. Conclusion: This survey highlights the need for improved availability of paediatric DATs and intubation equipment. Particular effort should be made to secure the more advanced equipment, and ensure the availability of a full size range for basic equipment. References: Major Complications of Airway Management in the United Kingdom, the 4th National Audit Project of the Royal College of Anaesthetists and the Difficult Airway Society, March 2011 Khan et al . Paediatric Difficult Airway Trolley Survey. Association of Paediatric Anaesthetists Peninsula Meeting Torquay 2011 Khan et al . Nationwide survey of Difficult Airway Trolleys in Paediatric Intensive Care, 24th Annual meeting of the European Society of Paediatric and Neonatal Intensive Care Standards for Children and Young People in Emergency Care Settings 2012, RCPCH